Interpretation of quranic verse 36:36 and human genome project (HGP) data: An analytical review based on science tawhidic concept - Mohd Noor A.Y.; Ab Rahman Z.; Mohd Kashim M.I.A.; Mohammed Zabidi A.F.; Mohd Mokhtar A. (Innovare Academics Sciences Pvt. Ltd, 2024)
The mechanisms by which biological males and females have been created in a precise speciesspecific design have always challenged the human minds. It has been mentioned in the Qur'an that male and female creations reflect a special sign from Allah for mankind to ponder over it. In contrast, using the recently completed HGP data, more than two dozens of scientific theories have been advanced to propose possible mechanisms by which males and females could probably originate in the past. Besides, the meaning of verse 36:36 has also been supported by many Quranic verses, including 2:164, 4:1, 7:189, 13:3, 16:8, 16:72, 30:20-21, 39:6, 42:11, 43:12, 45:4, 51:49, 53:45-46, 75:39, 78:8, and 92:3. This article aims to integrate between scientific and Quranic interpretation as well as to provide a better understanding of verse 36:36 when compared with the traditional exegesis approach. This study undertakes an analysis of scholars' view, promote intellectual discourse and scientific data as the main sources of reference by adopting the document analysis method. This analysis may, thus, serve as an example for those academicians who would like to Islamize their science curriculum or viceversa. The outcome of this article suggests that the evolution and continuity of sexual reproduction does not fit in nature; another theory predicts an extinction of the human males in future. Despite these, the male-female system prevails and, therefore, the origin and continuity of sex remain to be a great puzzle in today's science. The limitations of scientific theories, on the other hand, strengthen the Quranic verse 36:36 that states that, "Glory be to Him, who has created all the pairs of that which the earth produces, as well as of their own (human) kind (male and female), and of that which they know not." The powerful beginning word, "Glory be to Him" becomes more meaningful when the grandeur-scale complexities of male-females' creations are understood scientifically using the findings from HGP and other available data. 2020 Innovare Academics Sciences Pvt. Ltd. All rights reserved.